A study of mechanism for the prevention of cold inflow into Chimneys using wire mesh - Chu, Chi Ming; Sivakumar Kumaresan; Tham Heng Jin (Universiti Malaysia Sabah, 2013)
Cold air inflow has significant effect on a natural draft air cooled heat exchanger (NDACHE) chimney. To study the mechanism for the prevention of cold inflow into NDACHE chimney's, in total seven configuration of experiments were carried out In the prototype models for different heat loads at approximately 0.7SkW to 1.25kW. The effect of wire mesh screen on the chimney performance had also determined. Temperature and air velocity were measured for the configurations and heat loads. It was found that the top only, Top and Middle and Middle only installations were able to maintain draft velocity to within 3.0% of , the control experiment draft velocity in spite of the resistance of the mesh. It was also found that configurations utilizing mesh at the bottom had experienced a drop is draft velocity by up to 50% from the control. The smoke flow visualization tests clearly proved that cold air inflow phenomenon exits and can be countered with the installation of wire mesh at the top of the model. In the second phase of the project, the wire mesh of 3 different apertures and two chimney height were tested. Large aperture tended to allow more cold inflow and draft was directly proportional to chimney height. CFD runs were also done for the prototypes to explain the cause of wire mesh serving as repellent of cold inflow.